2021
DOI: 10.1200/op.20.00816
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Interprofessional Training Program to Improve Cancer Drug Therapy Safety

Abstract: PURPOSE: Drug therapy for cancer is a high-risk, high-volume clinical intervention that requires interprofessional teams. Given the complexity of anticancer drug therapy and safety concerns, an interdisciplinary team developed a novel training program for oncology registered nurses and pharmacists to improve cancer drug safety. METHODS: Participants completed preworkshop learning assessments and received access to web-based modules on six topics: hazardous drug handling, drug extravasation, hypersensitivity re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…Ortmeyer et al (2020) explored potential ways to deliver education about LC screening and found that participants in the group-based learning arm demonstrated greater total knowledge of LC screening in comparison to participants in lecture-based learning arm. These findings are in line with other educational interventions (Aebersold et al , 2021; Smit et al , 2021) and a systematic review (Zaher and Ratnapalan, 2012) which reported that group-based learning is a promising method for continuing professional development among HPCs and an effective means to increase and retain knowledge and potentially enhance inter-professional learning.…”
Section: Discussionsupporting
confidence: 88%
“…Ortmeyer et al (2020) explored potential ways to deliver education about LC screening and found that participants in the group-based learning arm demonstrated greater total knowledge of LC screening in comparison to participants in lecture-based learning arm. These findings are in line with other educational interventions (Aebersold et al , 2021; Smit et al , 2021) and a systematic review (Zaher and Ratnapalan, 2012) which reported that group-based learning is a promising method for continuing professional development among HPCs and an effective means to increase and retain knowledge and potentially enhance inter-professional learning.…”
Section: Discussionsupporting
confidence: 88%
“…Nineteen of the articles were published in the last five years. From the included papers eight focused on describing the need and competences of oncology healthcare professionals [ 3 , 4 , 6 , 9 , 32 35 ], three reviewed existing IPE [ 1 , 36 , 37 ] or the development and evaluation ( n = 17) of oncology interprofessional training [ 2 , 5 , 16 , 22 , 26 , 38 49 ]. The target groups of the IPE included nurses, pharmacists, physicians (medical oncology, surgical oncology, radiation oncology and palliative care), radiographers, technicians and staff with healthcare backgrounds such as psychology, occupational therapy and other support workers (such as social workers, chaplaincy, or administration staff in contact with oncology patients).…”
Section: Resultsmentioning
confidence: 99%
“…According to Head et al (2022) interprofessional collaborative practice is an essential component of quality healthcare in oncology [ 42 ]. Effective interprofessional care was seen as necessary to provide optimal care for patients [ 16 ], improve the safety of care delivery [ 38 ] and better outcomes of patient care [ 16 , 32 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such collaboration is essential for providing holistic care that takes into account the physical, psychological, and social needs of each patient with cancer in Nigeria. 18 Studies indicate that interprofessional collaboration in all aspects of cancer care, including administration of chemotherapy, 19 radiation therapy, 20 nursing care, 21 and cancer screening, 22 is vital for improving cancer outcomes.…”
Section: Introductionmentioning
confidence: 99%